PERPADUAN MODEL PEMBELAJARAN INKUIRI DENGAN POE (Predict-Observe-Explain) DALAM MENINGKATKAN HASIL BELAJAR SISWA SMP NEGERI 1 KAIRATUBackground: Learning outcomes are changes in student behavior due to learning. Behavior change is caused by achieving mast - Helmy Anggraeni Wakanno; P M. J Tuapattinaya; S I. A Salmanu (Program Studi Pendidikan Biologi FKIP Unpatti, 2019)
Background: Learning outcomes are changes in student behavior due to learning. Behavior change is caused by achieving mastery over a number of materials given in the teaching and learning process. These results can be in the form of changes in cognitive, affective and psychomotor aspects. This study aims to determine the increase in student learning outcomes of SMP Negeri 1 Kairatu on the excretion system in humans which is taught by applying the inquiry learning model combined with the POE (Predict-Observe-Explain) learning model. Method: The data obtained were analyzed descriptively. In this study, tests were given at the beginning and end of learning aimed to determine the level of student understanding of the material excretory system in humans. Non-test techniques in the form of affective assessment sheets and psychomotor assessment sheets. Results: Students' understanding of material in the Excretion System in humans prior to the implementation of the inquiry learning model combined with the POE (Predict-Observe-Explain) learning model is very low but, when integrating these two learning models there are many changes in student understanding that can be seen from their learning outcomes. Conclusion: There is an increase in student learning outcomes after conducting the teaching and learning process by using the inquiry learning model that is integrated with the POE (Predict-Observe- Explain) learning model on excretory material in humans